FAKTOR-FAKTOR DOMINAN DALAM PEMBENTUKAN LEMBAGA SOSIAL (Forum Penelitian Agro Ekonomi, 2016)
Local institutions have important role in the people-centered development vision, but such institutions establishment is carried out in absence of good social process.  This condition leads to poor performance of the institution, even it does not function at all, without any improvement in the long term.  Theoretical references, research as well as experience of establishing institutions suggest using some dominant factors in institutional development in order to get better performance.  There are at least six dominant factors in institutional establishment, namely the principles of democratic, participative, diffusion of innovation, and empowerment, besides the existence of conflict in the community and divergent orientation among residents.